Pollution Index Analysis of Seawater in Nickel Smelter Bantaeng's Port - Thahir, Muhammad Taufiq; Achmad, Fajrin (Universitas Islam Lamongan, 2023)
Good water quality conditions are significant for supporting the life of organisms and providing security for community activities. Water quality status determination is needed to monitor water quality pollution. Seawater quality is a critical aspect of environmental science and ecological research due to its profound impact on marine ecosystems, human health, and various community activities. It has been a significant concern because of its direct influence on marine ecosystems, human activities, and public health. This study aims to determine the pollution index referred to as physical-chemical-dissolved metal parameters in the nickel smelter port in Bantaeng Regency. A sampling of water quality was carried out at three sampling points. Then the results were compared with seawater quality standards for marine biota referred to the Keputusan Menteri Lingkungan Hidup No. 51/2004 on Seawater Quality Standards.Â Observation and analysis of water conditions are conducted in situ and ex-situ, with testing carried out at Ak-Manufaktur Laboratory and BBIHP Laboratory. The results of the pollution index calculation show that the waters around the nickel smelter port are in the moderately polluted category. The pollution index values were obtained in the moderately dirty variety at points 1: 8.515, 2: 9.652, and 3: 9.792.Â Environmental parameters still following quality standards for marine biota include temperature, pH, salinity, DO, and nickel (Ni).Keywords: pollution index; physical; chemical; metals; smelter